Perancangan Interaksi dan Antarmuka Pengguna Sistem Informasi Penjualan Nubek Coffee menggunakan Pendekatan Human Centered Design - Komang Agus Sathya Paramananda; Hanifah Muslimah Az-Zahra; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Nubek Coffee is a business that sells various types of coffee and other menu, where Nubek Coffee using internet to increase sales of its products. But in practice it did not work optimally, and sometimes found the problems, especially in serving customers and supplies with online systems. Based on this constraints, this research requires an information system design that is easy to use, and gives a comfortable experience to users, and can meet user needs. This research using the Human Centered Design method as a research method. The result of this research is a high-fidelity prototype. The evaluation of the solution design using the Usability Testing method and USE Questionnaire to manage the evaluation data. The prototype evaluation was testing 2 times, and in the second stage evaluation using 2 different design alternatives were applied. First solution design, found 12 problems on 10 pages from system. While in second design solution first alternative found 4 problems and the second alternative design solution found 2 problems. The usability appearance of the second solution design is better than the first stage solution design, although it needs to be made improvements. The conclusion of this research based on four indicators of the usability value obtained reach a value in the proper category and the system is in accordance with user needs in terms of Usefulness, Ease of Use, Ease of Learning, and Satisfaction.